Antioxidative Activity and Inhibition of Key Enzymes Linked to Type-2 Diabetes (α-Glucosidase and α-Amylase) by Khaya Senegalensis - Ibrahim Mohammed Auwal; Koorbanally Neil Anthony; Islam Md. Shahidul (Acta Pharmaceutica)
This study evaluated the in vitro antioxidative activity of Khaya senegalensis extracts and inhibitory effects of some solvent fractions on α-glucosidase and α-amylase activities. The stem bark, root and leaf samples of the plant were sequentially extracted with ethyl acetate, ethanol and water and then tested for antioxidative activity. Our findings revealed that the ethanolic extract of the root had the highest antioxidative activity. Solvent-solvent fractionation of the root ethanolic extract yielded a butanol fraction that showed higher antioxidative activity than other fractions. Furthermore, the butanol fraction had significantly higher (p < 0.05) α-glucosidase and α-amylase inhibitory activities with IC50 values of 2.89 ± 0.46 and 97.51 ± 5.72 μg mL-1, respectively. Enzyme kinetic studies indicated that the butanol fraction is a non-competitive inhibitor for α-glucosidase with an inhibition binding constant Ki of 1.30 μg mL-1 and a competitive inhibitor of α-amylase with a Ki of 7.50 μg mL-1. GC-MS analysis revealed that the butanol fraction contained two chromones, p-anilinophenol and 3-ethyl-5-(3- ethyl-(3H)-benzothiazol-2-ylidene)-2-(p-tolylvinylamino)- 4-thiazolidinone. Data obtained in the study suggest that the butanol fraction derived from the ethanolic extract of K. senegalensis root possessed excellent antioxidative as well as α-glucosidase and a-amylase inhibitory activities while chromones and/or p-anilinophenol could be the main bioactive compounds responsible for the observed activities.